Time perspective influence on management leadership styles and the mediating role of self-efficacy - Karim Gassemi; Julie Papastamatelou; Alexander Unger (Leadership, Education, Personality. An Interdisciplinary Journal, 2021)
We examined if time perspectives (TP) and the Deviation from a Balanced Time Perspective (DBTP-cf. Stolarski et al. Time Soc 20(3):346-363, 2011) have an effect on four types of Leadership Styles. Based on previous studies it was observed, that Self-Efficacy (SE) is determined by time perspectives (Epel et al. J Appl Soc Psychol 29(3):575-596, 1999). In particular, the transformational and transactional leadership styles could depend on higher self-efficacy of managers. We additionally tested if general self-efficacy (GSE) mediates the influence of time perspectives and the Deviation from a Balanced Time Perspective on Leadership Styles. We recruited a sample of former MBA-students, who now work in the middle management of German companies. We used the zimbardo time perspective inventory (ZTPI; Zimbardo and Boyd J Pers Soc Psychol 77(6):1271-1288, 1999), the Multifactor Leadership Questionnaire (MLQ) by Felfe and Goihl (Deutsche überarbeitete und ergänzte Version des Multifactor Leadership Questionnaire (MLQ) [German revised and extended version of the Multifactor Leadership Questionnaire (MLQ)], Zentrum für Umfragen Methoden und Analysen, Mannheim, 2002) and the general self-efficacy-scale by Schwarzer and Jerusalem (Generalized Self-Efficacy scale, Nfer-Nelson, Windsor, 1995). Past Positive orientation has no significant effect on any of the four leadership styles. The present hedonistic dimension enhances and the past negative orientation reduces the transformational leadership style. The present fatalistic orientation reduces the Transformational and transactional leadership styles, but enhances the laissez-faire leadership style. Moreover, future enhances the transformational and transactional leadership styles. DBTP reduces the transformational and transactional leadership styles. The mediator role of GSE was confirmed for the transformational and transactional leadership style. Managers' time perspectives are important for implementing an efficient leadership style.
Keywords: 330; Leadership styles; Managers; Self-efficacy; Time perspectives